Critical Framing: How Indonesian EFL Students Criticize Texts and Reconstruct Gender Equality in EFL Reading Class - Intan Nuvitasari; Pratiwi Retnaningdyah; Ahmad Munir (Linguistic, English Education and Art (LEEA) Journal, 2020)
This study was proposed to reveal how students criticize text and reconstruct gender equality through critical framing provided by the teacher. To conduct the research, field notes, recording on audio and video, and also students’ artifact (the result of discussion) were used. The text used in this research was the synopsis of Mustang (2015). The data was analyzed using critical discourse by looking at the influence of the linguistic used by the teacher and the text. The result showed that in criticizing text, female and male group is influenced by the linguistic used by the teacher and text and the power of the text and teacher can empower student to reconstruct gender equality and reject gender inequality, while male’s group was only influenced by the teacher. In addition, the linguistic used by the teacher also may lead them to relate with their society. In conclusion, female and males students are influenced by linguistic used in criticizing text. Keywords: Critical Framing, Gender Equality, Gender Inequality.